O impacto da visualização de informações na avaliação de competências: um mapeamento sistemático da literatura - CALEGARI CORRÊA, ANA CRISTINA; Kemczinski, Avanilde; Gasparini, Isabela; da Silva Hounsell, Marcelo (InfoDesign, 2022)
The competence assessment process contributes to talents management and organizational strategy. In this wise, Information Visualization may contribute to the adequate representation of data for analysis, leading to information previously not evident. A Systematic Literature Mapping was conducted to identify the state of the art in relation to the areas of Information Visualization and Competence Assessment. It was observed a predominance of the use of Information Visualization in the educational context, the use of graphics with low interactivity and lack of end-user involvement in project development. The result revealed a gap about the use of reference models for building Information Visualization solutions.